DEVELOPMENT OF SINGLE CROSS HYBRIDS FROM Momordica charantia BY FULL DIALLEL CROSSES - Al-asad, R. A. A.; Al-jebory, K. D. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
A field experiment was carried out in the plastic houses , College of Agricultural Engineering Ssciences , University of Baghdad during the spring season 2018. Six inbred lines of bitter gourd were entered into full diallel crosses, and planted during 2018-2019 season (six inbred lines symbolized as 1,2,3,4,5,6 +15 diallel hybrid + 15 reciprocal hybrid + control hybrid) according to randomized complete block design (RCBD) with three replicates, each experimental unit occupied 6 plants. Results revealed a significant differences among the genotypes in most of studied traits, The reciprocal hybrid 5×4 gave the highest values in leaf chlorophyll content (27.61 mlg mg-1), sex ratio (0.611), fruit setting percent (85.74%), and plant yield (2.005 kg), while the diallel hybrid 1×4 gave the highest values in leaves area (1.172 m2), sex ratio (0.747), fruits number (23.16), and plant yield (2.023 kg plant-1), Also the hybrid 6×4 gave the highest value in plant yield (2.105 kg plant-1), and the hybrid 1×3 gave the highest value in total phenols concentration (5.67 mlg gm-1), and the hybrid 2×3 gave the highest value in fruits weight (105.58 gm), charantin concentration (0.616 gm). Furthermore, many of reversal and reciprocal hybrids showed a positive hybrid abundance in the desired direction among the studied parameters, The reciprocal hybrid 6×4 gave the highest hybrid abundance in fruit weight (59.17%) and plant yield (120.3%), also the hybrid 5×4 gave the highest hybrid abundance in plant yield (69.99%).